Sosiolinguistik dalam Pembelajaran Bahasa Arab Melalui Maharah Kalam dengan Pendekatan Komunikatif - Nuha, Meisa Yasmin; Tatang (Ameena Journal, 2024)
This study aims to observe how the role of sociolinguistics in learning short story material by applying communicative schemes in one of the schools in Central Java. The methodology used is descriptive qualitative. The research data were obtained from the short story learning process that utilizes the maharah kalam method through the communicative scheme approach. The data collection techniques used included observation as well as interviews with teachers and students. The results show that short story learning in one of the school classes in Central Java can be implemented well using communicative schemes. The learning process takes place through three main stages, namely apperception, core activities, and closing, all of which are based on the principles of communicative schemes. In addition, sociolinguistics plays an important role in various aspects of learning, starting from the preparation of learning tools, the implementation of activities, to the use of language during the teaching and learning process. From the results and analysis of this study, it can be concluded that learning maharah kalam through short story materials makes a significant contribution to the study of sociolinguistics, especially in the application of communicative schemes in the classroom.